The reality and challenges of oil production, consumption and trade in the global economy - Slimane Dahou; Mostapha Ben Saha (Journal of Excellence for Economics and Management Research, 2018)
Oil production and trade is one of the main pillars of global economic relations because it is the most important source of energy and one of the most important sources of wealth in the world but under instability which is subject to many economic and political variables that challenged the world. Which will inevitably disappear, there have been significant challenges for producing countries to remain in the market and maintain their revenues from the oil trade. Developments in the alternative energy industry, in general and renewable ones in particular, pose a major challenge to the producing countries, including Algeria, especially as it depends entirely on its economy on oil exports, which necessitates benefiting from the large oil revenues it enjoys in financing productive sectors such as the agricultural and industrial sectors Which contributes to the diversification of economic activity and the elimination of the grip of oil, in addition to the establishment of a strong strategy to support renewable energies and the gradual transition towards them.